Amplification of PCR products in excess of 600 base pairs using DNA extracted from decalcified, paraffin wax embedded bone marrow trephine biopsies. Issue 1 (1st February 2000) - Wickham, C L; Boyce, M; Joyner, M V; Sarsfield, P; Wilkins, B S; Jones, D B; Ellard, S
Abstract : Aims —To establish a robust method of extracting DNA from paraffin wax embedded bone marrow trephine (PBMT) biopsies for the amplification of relatively long polymerase chain reaction (PCR) products. Method —Xylene and ethanol were used to remove paraffin wax from eight formalin fixed, EDTA decalcified PBMT biopsies and DNA extraction was performed using a Qiagen QIAamp tissue kit. The DNA samples were amplified using nine different PCR primers sets, including those used to detect chromosomal translocations t(11;14) and t(14;18), and clonal B cell populations. A t(11;14) PCR product of approximately 600 base pairs (bp) was sequenced using dye terminator cycle sequencing. Results— All eight DNA samples extracted from PBMT biopsies were amplified successfully to generate DNA fragments up to 643 bp in length. Chromosomal translocations and immunoglobulin gene rearrangements were detected by PCR in some of the samples. Sequencing of the t(11;14) PCR product demonstrated the presence of chimaeric sequences, which included both bcl-1 and immunoglobulin heavy chain (IgH) gene sequences, consistent with the presence of this translocation. Conclusions— This method enables PCR analyses of PBMT biopsies that were not previously possible, offering the prospect of improved accuracy of diagnosis and the monitoring of patients with bone marrow disease.